Airflow simulation and measurement of brake wear particle emissions with a novel test rig - A.B. Sanuddin; Kosarieh, S.; Gilkeson, C.A.; Brooks, P.C.; Barton, D.C. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Particle emissions generated by the braking systems of road vehicles represents a significant non-exhaust contributor. Fine particles such as these are transported through airborne routes. They are known to adversely affect human health and currently there are no policies in place to regulate them. Before this issue can be addressed, it is important to characterise brake wear debris which is the purpose of this study. A newly-developed test rig consisting of a closed but ventilated enclosure surrounds a brake dynamometer equipped with a cast iron rotor. A sampling probe was made in accordance with the isokinetic principles in order to withdraw a representative aerosol sample from the outlet duct. Measurements of real-time particulate numbers and mass distributions are recorded using a Dekati ELPI®+ unit and the brake materials were tested under drag-braking conditions. Prior to measurements, Computational Fluid Dynamics (CFD) simulations were performed to investigate the most suitable sampling points used in the experiments. Preliminary experimental results show that there is a noticeable increase in particle numbers, compared to background levels, with a corresponding change in the mass distribution; coarser particles become more prominent during these braking events. These results provide confidence in the performance of the test rig and its ability to measure airborne brake wear debris in order to compare emissions from various friction pairs.